Перспективи і проблеми становлення інститутів громадянського суспільства в Україні - Лаба, О.; Laba, O. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано перспективи становлення інститутів громадянського суспільства в Україні. Обґрунтовано позицію, що в реальному суспільному житті громадянське суспільство та правова держава є взаємопов’язаними інститутами, функціонування яких забезпечується верховенством закону, що надійно гарантує та захищає права і свободи громадян. На основі інтеграції зусиль громади і держави в Україні має бути сформовано інституційну партнерську систему «держава – громадянське суспільство». Today the general interest to the problems of civil society has grown considerably. Quality and rates of democratization of society have crucial importance in an assessment of changes in Ukraine from the point of view of image of the country in the interstate relations and influences of world institutes. It has been proved in the article that in real public life civil society and the constitutional state are the interconnected institutes which functioning is provided with the rule of law, and it reliably guarantees and protects the rights and freedoms of citizens. The institutional partner system «the state – civil society» ought to be created on the basis of integration of efforts of society and the state in Ukraine. According to the author’s point of view the elements of civil society are the following: existence of the democratic constitutional state; self-management of the voluntary organizations, associations and individuals; variety of forms of ownership; market economy; pluralism of ideologies and political views; multiparty system; access to the participation in the state and public affairs for all citizens; mutual responsibility of the state and citizens for the implementation of democratically adopted laws; the developed civil political culture and conscience; the priority of the citizens’ rights over the state laws; control of society over the activity of government bodies; existence of the developed social structure and variety of social initiatives.
Prospects and Problems of Formation of Institutes of Civil Society in Ukraine.
Keywords: держава; громадянське суспільство; демократизація суспільства; демократія; верховенство права; верховенство закону; державна влада; права людини; state; civil society; democratization of society; democracy; rule of law; government; human rights